Poemas entre músicas: dialogia melopoética e(m) uma didática contemporânea - Robson Coelho Tinoco; Marília de Alexandria (Estudos de Literatura Brasileira Contemporânea)
Under the dialogical notion of a given poetic-musical language can be structured a didactic process with activities that best relate literature and music (popular and classical). Referring to hearing music and literary reading, the teaching aims to understand students as individuals represented by a strong dialogic ethical and aesthetic reception. In that current context historical of globalization and multise- miotic informations it is believed that, in the measure in the individual-student notices the due relation / integration of those levels, the contact with the implicit musicality in the verses of poems will make possible that she is apprehended bet- ter until as contemporary melopoetic element. With such concern, and leaning on in analyses of Mikhail Bakhtin, Octavio Paz, José Miguel Wisnik, Luiz Tatit e Jusamara Souza, the theoretical foundations of the didatic process consider, basi- cally, a conception dialogical and interactionist of that of those artistics language).